Coal miner’s day in India: a reflection on health risks and legislation - Sahanaa, Chandar; Murugan, Yuvaraja (International Journal Of Community Medicine And Public Health, 2023)
Coal mining is a hazardous profession in India that exposes workers to a range of health risks, including respiratory diseases, skin disorders, hearing loss, and injuries. The coal miner’s day, observed on May 4th every year, commemorates the hard work and sacrifices of coal miners. The Mines Act, 1952, and its associated regulations mandate the provision of medical facilities, safety and health measures, and rescue stations and trained personnel for the rescue of workers. The Coal Mines (Conservation and Development) Act, 1974, mandates the conservation of coal resources and the development of coal mines while ensuring the safety and health of workers. However, the implementation of these laws has been inadequate in many cases, leading to a high prevalence of occupational diseases among coal miners. The lack of proper implementation of safety and health regulations has been identified as a key factor contributing to the high prevalence of occupational diseases. Additionally, the existing regulations do not address the specific safety and health issues associated with the use of automation and robotics in mining. To safeguard the health and safety of coal miners, more efforts are needed to ensure the effective implementation of these laws and to provide adequate medical support and rehabilitation services. Prioritizing the health and well-being of coal miners can pay tribute to their contribution to society while promoting a safer and healthier workplace for all.